THE POTENTIAL OF IVAN BAHRIANYI’S WORKS IN SCHOOL EDUCATION - Voitovych, Diana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
Annotation. The article explores the potential of Ivan Bahrianyi’s literary works, in particular his novel “Tyhrolovy” in shaping the personality of modern school students. Special attention is given to the slow reading technique, the use of innovative teaching methods, the organization of active dialogue during lessons, and the development of key student competences. The educational, moral, and worldview significance of Bahrianyi’s works is analyzed, particularly in fostering national consciousness, civic resposibility, and ethical values. Methodological guidelines for integrating Bahrianyi’s works into school literature education are proposed, promoting critical thinking, emotional intelligence, and creativity.